STAGES OF FORMATION AND DEVELOPMENT OF THE STUDENT GROUP. THE ROLE OF THE STUDENT GROUP IN THE EDUCATIONAL PROCESS - Taylonov Bakhtiyor Numonovich,; Tulaganov Karim Olimjonovich,; Hamidullayev Rustam Fayzullayevich,; Pulatov Sarvar Mustafayevich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. A team is a group of students who strive for a common goal and are united for joint activities. Its general principles are: setting requirements, educating activists, organizing prospects in educational, labor, socio-political and mass cultural activities, forming a healthy public opinion, creating and strengthening positive traditions. This article describes the stages of formation and development of a student team. Information is provided about the role of the student team in the educational process.